Kadar Flavonoid Total dan Aktivitas Tabir Surya Ekstrak Kulit Edamame (Glycine max (L.) Merr.) - Kristiningrum, Nia; Fadhil, Anfaq Syahriyal; Retnaningtyas, Yuni; Pangaribowo, Dian Agung; Pratoko, Dwi Koko; Sary, Indah Purnama; Wulandari, Lestyo (Journal of Agropharmacy, 2026)
Edamame pod waste (Glycine max (L.) Merr.) is often underutilized despite its potential to contain bioactive compounds such as flavonoids, which possess antioxidant and ultraviolet (UV) protective properties. Excessive exposure to UV radiation can cause various skin problems, including premature aging and increased risk of skin cancer, highlighting the need for safe natural sunscreen agents. This study aimed to determine the total flavonoid content and Sun Protection Factor (SPF) value of ethanol extract of edamame pods in vitro. Extraction was performed using the maceration method with 96% ethanol. Total flavonoid content was determined using UV–Vis spectrophotometry with AlCl₃ and CH₃COOK reagents, using quercetin as a standard at a maximum wavelength of 446 nm. The SPF value was evaluated in vitro using a UV–Vis spectrophotometer at wavelengths of 290–320 nm with 5 nm intervals and calculated using the Mansur equation. All measurements were performed in triplicate. The results showed that the ethanol extract of edamame pods contained a total flavonoid content of 5.177 ± 0.432 mg QE/g extract. At a concentration of 1500 µg/mL, the extract exhibited the highest SPF value of 17.22, which is categorized as ultra protection against UVB radiation. These findings indicate that the ethanol extract of edamame pods (Glycine max (L.) Merr.) has potential as a natural source of flavonoids and a photoprotective agent for sunscreen or cosmetic formulations.